Comparison of revascularization with conservative medical treatment in maintenance dialysis patient with coronary artery disease: a systemic review and meta-analysis - Zheng, Ling; Wang, Xiang; Zhong, Yu-cheng (Frontiers in Cardiovascular Medicine, 2023)
Background: The primary cause of death among maintenance dialysis patients is coronary artery disease. However, the best treatment option has not yet been identified. Methods: Different online databases and references to associated articles were looked up from the beginning to October 12, 2022. We selected the studies that compared revascularization [percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG)] with medical treatment (MT) alone among maintenance dialysis patients with CAD. The outcomes evaluated were long-term all-cause mortality, long-term cardiac mortality and the incidence rate of bleeding events. In addition, revascularization strategy, CAD type and the number of diseased vessels were all taken into account in subgroup analyses. Results: Eight studies with 1685 patients in total were selected for the study. Our findings suggested that revascularization was connected with lower long-term all-cause mortality (RR = 0.73, 95%CI = 0.63–0.84) and long-term cardiac mortality (RR = 0.55, 95%CI = 0.40–0.76) but similar incidence rate of bleeding events (RR=0.93, 95%CI = 0.65–1.32) compared with MT. However, subgroup analyses indicated that PCI was linked with decreased long-term all-cause mortality (RR = 0.72, 95%CI = 0.62–0.84) compared with MT but CABG did not significantly differ from MT in terms of long-term all-cause mortality (RR = 0.91, 95%CI = 0.57–1.46). Revascularization also showed lower long-term all-cause mortality compared with MT among patients with stable CAD, single-vessel disease (RR = 0.61, 95%CI = 0.49–0.77) and multivessel disease, but did not reduce long-term all-cause mortality among patients with ACS (RR = 0.90, 95%CI = 0.38–2.12). Conclusion: Among patients on maintenance dialysis with CAD, revascularization, especially PCI, could reduce long-term all-cause mortality and long-term cardiac mortality but not increase the incidence rate of bleeding events.